A high temperature resistant soft flame retardant polyvinyl chloride material and preparation method thereof
By using high-part plasticizer and magnesium, aluminum, zinc intercalated hydrotalcite and other components in polyvinyl chloride materials, the problem of insufficient thermal stability, flexibility and mechanical properties of the material is solved, and high-performance Preparation of high temperature resistant soft flame retardant polyvinyl chloride materials.
Patent Information
- Application Number
- CN202410595918.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-14
AI Technical Summary
It is difficult for existing polyvinyl chloride materials to have high thermal stability, flexibility and mechanical properties at the same time, and the amount of existing stabilizers can be added is limited, which affects the processing performance of the material.
The interlayer structure of magnesium aluminum zinc intercalation hydrotalcite, flame retardant, lubricant and antioxidant is adopted to coordinate the interlayer structure of magnesium aluminum zinc intercalation hydrotalcite and The migration effect of antioxidants improves the thermal stability and dispersion of the material.
The prepared high-temperature resistant soft flame retardant polyvinyl chloride material has excellent thermal stability, flexibility, flame retardant properties and mechanical properties. It can withstand low-temperature bending -40℃ and resistant to high temperature of 125℃, exceeding the provisions of industry standard UL758-2022. .
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of cables, and in particular to a high temperature resistant, soft, flame retardant polyvinyl chloride material and a preparation method thereof. Background Art
[0002] As of September 2022, China has put into operation more than 50GW of power storage projects, of which new energy storage projects have reached 6.6GW. Energy storage has now become a national strategic emerging industry with high technology content and great growth potential. Energy storage cables play the role of signal and data transmission and power supply in the entire energy storage industry chain. Energy storage systems require stable and reliable signal connections, which places very strict requirements on the functionality of energy storage cables in terms of high temperature resistance, pressure resistance, aging resistance, electromagnetic shielding, flame retardancy, etc.
[0003] With the development of the energy storage industry, the entire industry has put forward new requirements for the long-term charging and discharging conditions of energy storage cables, and the temperature resistance requirements of energy storage cables have also increased accordingly.
[0004] Chinese patent CN102719040A discloses a wear-resistant and flame-retardant polyvinyl chloride insulation and sheath material, the disclosed mass ratio of which is: 100 parts of polyvinyl chloride resin with a degree of polymerization of 2500; 40 parts of trioctyl trimellitate (TOTM), 20 parts of diisononyl phthalate (DINP), 20 parts of EVA resin, 8 parts of barium zinc composite stabilizer, 5 parts of antimony trioxide, 2.5 parts of zinc borate, 15 parts of aluminum hydroxide, 7.5 parts of calcined kaolin, 30 parts of heavy calcium carbonate, 1.5 parts of butyl stearate, 0.6 parts of stearic acid, and 0.6 parts of polyethylene wax. However, the content of barium-zinc composite stabilizer used in its formula is relatively low, and the thermal stability and aging resistance of the prepared wear-resistant and flame-retardant polyvinyl chloride insulation and sheath materials are poor. The plasticizer has a low flash point and large volatilization loss during processing and testing, resulting in poor flexibility, aging resistance and thermal stability of the wear-resistant and flame-retardant polyvinyl chloride insulation and sheath materials.
[0005] However, the amount of stabilizer that can be added in the prior art is limited, and if the amount is too high, it is easy to be unevenly dispersed, affecting the processing performance of the material, and further resulting in a decrease in the flexibility and mechanical properties of the polyvinyl chloride material. Summary of the invention
[0006] In order to solve the problem that existing polyvinyl chloride materials are difficult to have high thermal stability, flexibility and mechanical properties at the same time, the present application provides a high temperature resistant soft flame retardant polyvinyl chloride material and a preparation method thereof.
[0007] In the first aspect, the present application provides a high temperature resistant soft flame retardant polyvinyl chloride material:
[0008] A high temperature resistant soft flame retardant polyvinyl chloride material, whose raw materials include, by weight, 100 parts of PVC resin, 80-95 parts of plasticizer system, 5-15 parts of magnesium aluminum zinc intercalated hydrotalcite, 0.1-1 parts of antioxidant, 10-15 parts of filler, 13-50 parts of flame retardant and 0.2-0.6 parts of lubricant.
[0009] The magnesium-aluminum-zinc intercalated hydrotalcite can combine with hydrogen chloride released by the decomposition of PVC and form a complex with unstable chlorine atoms in PVC, thereby coupling the PVC molecular chain and inhibiting the self-catalytic removal of HCl by PVC. By adopting the above technical scheme and using a larger number of plasticizers, the larger number of plasticizers promotes the dispersibility and compatibility of the magnesium-aluminum-zinc intercalated hydrotalcite, antioxidant, filler and flame retardant in PVC resin, so that the prepared high-temperature resistant, soft and flame-retardant polyvinyl chloride material has good thermal stability, flexibility, flame retardancy, aging resistance and mechanical properties.
[0010] Furthermore, the magnesium-aluminum-zinc intercalated hydrotalcite has an interlayer structure, is heat-resistant, heat-insulating and has good chemical stability. The antioxidant can migrate into the interlayer structure of the magnesium-aluminum-zinc intercalated hydrotalcite, further improving the stability of the antioxidant, and the two form a good compatibility effect, thereby improving the thermal stability and aging resistance of the high-temperature resistant, soft, flame-retardant polyvinyl chloride material.
[0011] The high temperature resistant, soft, flame-retardant polyvinyl chloride material of the present application can withstand bending at a low temperature of -40°C, and can withstand high temperatures of 125°C, which is better than the provisions of the industry standard UL758-2022 "Safety Standards for Electrical Wiring Wires and Cables".
[0012] Preferably, the plasticizer is at least one of polyester plasticizer, epoxidized soybean oil and EVA.
[0013] Preferably, the plasticizer is a composition of EVA and polyester plasticizer in a mass ratio of (0.1-1.2):1;
[0014] The polyester plasticizer is at least one of polyester plasticizer W-797, tetraoctyl pyromellitate, trioctyl trimellitate, di(2-propylheptyl)phthalate, and undecyl phthalate.
[0015] By adopting the above technical solution, the types of plasticizers and polyester plasticizers are optimized to further improve the flexibility of the high temperature resistant soft flame retardant polyvinyl chloride material.
[0016] High vinyl acetate content EVA is used to partially replace the plasticizer. EVA is more stable and not easy to volatilize, which reduces the volatilization of plasticizers during aging, improves the heat resistance, toughness and impact resistance of vinyl chloride materials, and further improves the thermal stability and flexibility of high temperature resistant soft flame retardant polyvinyl chloride materials.
[0017] Preferably, the lubricant is at least one of neutral ester wax, oxidized polyethylene wax, pentaerythritol stearate, liquid paraffin, solid paraffin, polyethylene wax, E wax and stearic acid.
[0018] Preferably, the lubricant is a combination of neutral ester wax and oxidized polyethylene wax.
[0019] Preferably, the lubricant is 0.1-0.3 parts of neutral ester wax and 0.1-0.3 parts of oxidized polyethylene wax;
[0020] The neutral ester wax is at least one of dicarboxylic acid esters of saturated fatty alcohols, butyl stearate, glyceryl monostearate, and pentaerythritol stearate.
[0021] By adopting the above technical solution and using lubricants, the friction heat generated during the processing is reduced, which indirectly improves the stability. The type of lubricant is selected to further improve the thermal stability of the high-temperature resistant, soft, flame-retardant polyvinyl chloride material.
[0022] Preferably, the amount of the magnesium-aluminum-zinc intercalated hydrotalcite is 10-15 parts.
[0023] By adopting the above technical solution, the amount of magnesium-aluminum-zinc intercalated hydrotalcite is optimized, and the thermal stability and mechanical properties of the high-temperature resistant, soft, flame-retardant polyvinyl chloride material are further improved.
[0024] If the content of magnesium-aluminum-zinc intercalated hydrotalcite is too little, the thermal stability of high-temperature-resistant, soft, flame-retardant polyvinyl chloride materials will not be improved well, and the aging resistance will decrease. If the content of magnesium-aluminum-zinc intercalated hydrotalcite is too much, it will easily agglomerate and disperse poorly in PVC, and the tensile strength and elongation at break of high-temperature-resistant, soft, flame-retardant polyvinyl chloride materials will tend to decrease.
[0025] Preferably, the magnesium-aluminum-zinc intercalated hydrotalcite is treated with a treatment solution for 20-30 hours, and then filtered, washed, and dried to obtain a modified magnesium-aluminum-zinc intercalated hydrotalcite;
[0026] The treatment liquid includes 1-3 kg / L of dopamine, 0.3-0.6 kg / L of epoxy silane coupling agent and 1-1.5 kg / L of ammonium persulfate, and the pH value is adjusted to 8-9.
[0027] By adopting the above technical scheme, the magnesium-aluminum-zinc intercalated hydrotalcite is treated with a treatment liquid, and the surface of the magnesium-aluminum-zinc intercalated hydrotalcite is modified with polydopamine and a silane coupling agent to improve the dispersibility and precipitation resistance of the magnesium-aluminum-zinc intercalated hydrotalcite in the PVC substrate, thereby improving the thermal stability and mechanical properties of the high-temperature resistant, soft, flame-retardant polyvinyl chloride material.
[0028] Preferably, the flame retardant is 3-9 parts of antimony trioxide, 5-25 parts of magnesium hydroxide and 5-16 parts of aluminum hydroxide;
[0029] The filler is at least one of calcium carbonate, kaolin and talc;
[0030] The antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenol) phosphite and β-dodecylthiopropionate pentaerythritol ester.
[0031] By adopting the above technical solutions, the types of flame retardants, fillers and antioxidants are optimized, and the thermal stability, flexibility, aging resistance and flame retardancy of high temperature resistant soft flame retardant polyvinyl chloride materials are further improved.
[0032] In a second aspect, the present application provides a method for preparing a high temperature resistant, soft, flame retardant polyvinyl chloride material:
[0033] A method for preparing a high temperature resistant, soft, flame retardant polyvinyl chloride material, the preparation steps are as follows:
[0034] The raw materials of the high temperature resistant soft flame retardant polyvinyl chloride material are mixed and stirred at high speed to form a mixture;
[0035] The mixture is melt-extruded, granulated and cooled to prepare a high-temperature resistant, soft and flame-retardant polyvinyl chloride material; the temperature of the melt-extrusion is 130-185°C.
[0036] By adopting the above technical scheme, a high-temperature resistant soft flame-retardant polyvinyl chloride material with good thermal stability, flexibility, flame retardancy and mechanical properties is prepared.
[0037] Preferably, the preparation process of the mixture is to mix PVC resin, polyester plasticizer, magnesium aluminum zinc intercalated hydrotalcite, antioxidant, filler, flame retardant and lubricant, stir at high speed, and heat to 115-125°C; then cool to 70-90°C, add EVA, stir and mix, and obtain the mixture.
[0038] By adopting the above technical solution and adding EVA at a lower temperature, the dispersibility of EVA in PVC is improved, the bridging of powder is avoided, and the flexibility, mixing effect and production speed of the high temperature resistant soft flame retardant polyvinyl chloride material are improved.
[0039] In summary, this application has the following beneficial effects:
[0040] 1. The present application discloses a high-temperature resistant, soft, flame-retardant polyvinyl chloride material, which adopts PVC resin, a relatively high proportion of plasticizer, magnesium-aluminum-zinc intercalated hydrotalcite with an interlayer structure, a flame retardant, a lubricant and an antioxidant to cooperate with each other, so that the prepared high-temperature resistant, soft, flame-retardant polyvinyl chloride material has good thermal stability, flexibility, flame retardancy and mechanical properties.
[0041] 2. The plasticizer is preferably a combination of EVA and polyester plasticizer in a mass ratio of (0.1-1.2):1, which further improves the stability and plasticizing effect of the high temperature resistant soft flame retardant polyvinyl chloride material.
[0042] 3. The magnesium-aluminum-zinc intercalated hydrotalcite is preferably treated with a treatment liquid so that the surface of the magnesium-aluminum-zinc intercalated hydrotalcite is modified with polydopamine and a silane coupling agent, thereby improving the dispersibility and precipitation resistance of the magnesium-aluminum-zinc intercalated hydrotalcite in the PVC substrate, and further improving the thermal stability, flexibility and mechanical properties of the high-temperature resistant, soft and flame-retardant polyvinyl chloride material. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is the DSC-TG graph of the high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 4 to 6 and Example 1.
[0044] Figure 2 It is a comparison chart of the tensile strength, elongation at break, and the retention rate of tensile strength and elongation at break after aging (158°C×168h) of the high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 4 to 6 and Example 1.
[0045] Figure 3 It is the DSC-TG graph of the high temperature resistant soft flame retardant polyvinyl chloride material of Example 13 to Example 15 and Example 1.
[0046] Figure 4 It is a comparison chart of the tensile strength, elongation at break, and the retention rate of tensile strength and elongation at break after aging (158°C×168h) of the high-temperature resistant, soft, flame-retardant polyvinyl chloride materials of Examples 13 to 15 and Example 1.
[0047] Description of reference numerals:
[0048] 1. TG graph of Example 4 (the plasticizer is TOTM, and the amount of magnesium aluminum zinc intercalated hydrotalcite is 12.5); 2. TG graph of Example 5 (the plasticizer is polyester plasticizer W-797);
[0049] 3. TG diagram of Example 1 (the plasticizer is tetraoctyl pyromellitate);
[0050] 4. TG graph of Example 6 (the plasticizer is a composition of tetraoctyl pyromellitate and EVA in a mass ratio of 1:1);
[0051] 5. DSC graph of Example 4 (the plasticizer is TOTM, and the amount of magnesium aluminum zinc intercalated hydrotalcite is 12.5); 6. DSC graph of Example 5 (the plasticizer is polyester plasticizer W-797);
[0052] 7. DSC graph of Example 1 (the plasticizer is tetraoctyl pyromellitate);
[0053] 8. DSC graph of Example 6 (the plasticizer is a composition of tetraoctyl pyromellitate and EVA in a mass ratio of 1:1);
[0054] 9. TG graph of Example 13 (Mg-Al-Zn intercalated hydrotalcite dosage 5);
[0055] 10. TG diagram of Example 14 (Mg-Al-Zn intercalated hydrotalcite dosage 10);
[0056] 11. TG diagram of Example 15 (Mg-Al-Zn intercalated hydrotalcite dosage 15);
[0057] 12. DSC graph of Example 13 (Mg-Al-Zn intercalated hydrotalcite dosage 5);
[0058] 13. DSC graph of Example 14 (Mg-Al-Zn intercalated hydrotalcite dosage 10);
[0059] 14. DSC chart of Example 15 (the amount of magnesium-aluminum-zinc intercalated hydrotalcite is 15). DETAILED DESCRIPTION
[0060] raw material
[0061] PVC resin (polymerization degree 1800±50), tetraoctyl pyromellitate (flash point ≥270℃), octyl trimellitate (flash point ≥265℃), TOTM (flash point ≥240℃), EVA (ARLANXEO, EVM500, vinyl acetate content 50%), magnesium aluminum zinc intercalated hydrotalcite (vacuum degree 500m 2 / kg, average particle size 4μm, activation degree>95%), tris(hydroxymethyl)aminomethane hydrochloride (white crystalline powder, purity 99%), epoxy silane coupling agent (colorless transparent liquid, flash point>110℃), dopamine (purity 99%, white powder), barium zinc stabilizer (yellow clear liquid, specific gravity 1.0g / cm 3 , freezing point at -15℃), calcium carbonate (D50≤1.8μm), antimony trioxide (antimony content ≥99.8%), magnesium hydroxide (magnesium oxide content ≥60%, D50≤1.8μm), aluminum hydroxide (D50≤1.8μm), kaolin (D50:2.1±0.5μm), talc (D50:2.5±0.5μm), oxidized polyethylene wax (melting point 101±2℃).
[0062] Preparation example of intermediate
[0063] Preparation Example 1, a modified magnesium-aluminum-zinc intercalated hydrotalcite, the preparation process of which is as follows:
[0064] The magnesium-aluminum-zinc intercalated hydrotalcite was immersed in the treatment solution (the mass ratio of the magnesium-aluminum-zinc intercalated hydrotalcite to the treatment solution was 1:8), stirred at 300 rpm at room temperature for 25 hours, filtered, washed, and dried in a vacuum oven at 40° C. for 8 hours to prepare the modified magnesium-aluminum-zinc intercalated hydrotalcite.
[0065] A treatment solution is prepared using dopamine, 3-glycidyloxypropyltrimethoxysilane, ammonium persulfate, tris(hydroxymethyl)aminomethane hydrochloride and water; the treatment solution includes 2kg / L of dopamine, 0.5kg / L of 3-glycidyloxypropyltrimethoxysilane and 1.2kg / L of ammonium persulfate, and tris(hydroxymethyl)aminomethane hydrochloride is used to adjust the pH value of the aqueous solution to 8.5.
[0066] Preparation Example 2, a modified magnesium-aluminum-zinc intercalated hydrotalcite, the preparation process of which is as follows:
[0067] The magnesium-aluminum-zinc intercalated hydrotalcite was completely immersed in the treatment solution, stirred at 300 rpm for 30 hours at room temperature, filtered, washed, and dried in a vacuum oven at 50° C. for 8 hours to prepare the modified magnesium-aluminum-zinc intercalated hydrotalcite.
[0068] A treatment solution is prepared using dopamine, 3-glycidyloxypropyltrimethoxysilane, ammonium persulfate, tris(hydroxymethyl)aminomethane hydrochloride and water; the treatment solution includes 3kg / L of dopamine, 0.6kg / L of 3-glycidyloxypropyltrimethoxysilane and 1.5kg / L of ammonium persulfate, and tris(hydroxymethyl)aminomethane hydrochloride is used to adjust the pH value of the aqueous solution to 8.
[0069] Preparation Example 3, a modified magnesium-aluminum-zinc intercalated hydrotalcite, the preparation process of which is as follows:
[0070] The magnesium-aluminum-zinc intercalated hydrotalcite was completely immersed in the treatment solution, stirred at 300 rpm at room temperature for 20 hours, filtered, washed, and dried in a vacuum oven at 60° C. for 8 hours to prepare the modified magnesium-aluminum-zinc intercalated hydrotalcite.
[0071] A treatment solution is prepared using dopamine, 1,3-bis(3-glycidylpropyl)-1,1,3,3-tetramethyldisiloxane, ammonium persulfate, tris(hydroxymethyl)aminomethane hydrochloride and water; the treatment solution includes 1 kg / L of dopamine, 0.3 kg / L of 1,3-bis(3-glycidylpropyl)-1,1,3,3-tetramethyldisiloxane and 1 kg / L of ammonium persulfate, and tris(hydroxymethyl)aminomethane hydrochloride is used to adjust the pH value of the aqueous solution to 9.
[0072] Example
[0073] Example 1, a high temperature resistant soft flame retardant polyvinyl chloride material, using raw materials as shown in Table 1, and its preparation process is as follows: PVC resin, plasticizers other than EVA, magnesium aluminum zinc intercalated hydrotalcite, antioxidants, fillers, flame retardants and lubricants (specifically as shown in Table 1) are poured into a high-speed stirring tank, and stirred at a speed of 50r / min. The intense friction between the blade and the raw material generates heat to heat the raw material. When the temperature of the material in the tank rises to 115°C, the plasticizer is completely absorbed by the PVC resin; then the temperature is cooled to 80°C, EVA is added, stirred and mixed to form a mixture, and then the material is discharged, and the temperature difference of the material during the discharge is controlled within 5°C.
[0074] The mixture was extruded through a two-stage counter-rotating twin-screw extruder, with extrusion temperatures as follows: upper machine temperature setting: zone 1 150°C, zone 2 160°C, zone 3 170°C, zone 4 175°C, zone 5 185°C, zone 6 170°C, die head 165°C; lower machine temperature setting: zone 1 130°C, zone 2 140°C, die head 150°C.
[0075] After extrusion, the melt is granulated, cooled, and screened out with a vibrating screen to remove sticky particles, so as to prepare pellets of high-temperature resistant, soft, flame-retardant polyvinyl chloride material.
[0076] Embodiment 2 to Embodiment 3 are a kind of high temperature resistant soft flame retardant polyvinyl chloride material. The difference from Embodiment 1 is that the types of raw materials, raw material weights and preparation process parameter settings are different, as shown in Table 1.
[0077] Table 1. List of raw material types, raw material weights and preparation process parameter settings used in the preparation process of high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 1 to 3
[0078]
[0079]
[0080]
[0081] In Table 1, the neutral ester waxes used in Examples 1 and 2 are both butyl stearate; the neutral ester wax used in Example 3 is a composition of glyceryl monostearate and pentaerythritol stearate in a mass ratio of 1:1.
[0082] Examples 4 to 12 are a high temperature resistant, soft, flame retardant polyvinyl chloride material. The difference from Example 1 is that the types of plasticizers are set differently, as shown in Table 2.
[0083] Table 2. List of plasticizer types used in the preparation process of high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 4 to 12 and Example 1
[0084]
[0085] Examples 13 to 15 are high temperature resistant, soft, flame retardant polyvinyl chloride materials. The difference from Example 1 is that the dosage of magnesium aluminum zinc intercalated hydrotalcite is set differently, as shown in Table 3.
[0086] Table 3. Table of settings for the amount of magnesium-aluminum-zinc intercalated hydrotalcite used in the preparation process of high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 13 to 15 and Example 1
[0087]
[0088] Example 16, a high temperature resistant soft flame retardant polyvinyl chloride material, is different from Example 1 in that the modified magnesium aluminum zinc intercalated hydrotalcite of Preparation Example 1 is used to replace the magnesium aluminum zinc intercalated hydrotalcite in an equal amount.
[0089] Embodiment 17 to Embodiment 18, a kind of high temperature resistant soft flame retardant polyvinyl chloride material, is different from Embodiment 16 in that the modified magnesium aluminum zinc intercalated hydrotalcite adopts the modified magnesium aluminum zinc intercalated hydrotalcite of Preparation Example 2 to Preparation Example 3 in sequence.
[0090] Example 19, a high temperature resistant soft flame retardant polyvinyl chloride material, differs from Example 1 in that the flame retardant is 41.5 kg of aluminum hydroxide.
[0091] Comparative Example
[0092] Comparative Example 1 is a high temperature resistant soft flame retardant polyvinyl chloride material, which is different from Example 1 in that 75 kg of tetraoctyl pyromellitate is used.
[0093] Comparative Example 2 is a high temperature resistant soft flame retardant polyvinyl chloride material, which is different from Example 1 in that 3.5 kg of magnesium aluminum zinc intercalated hydrotalcite and 75 kg of tetraoctyl pyromellitic acid are used.
[0094] Comparative Example 3, a high temperature resistant soft flame retardant polyvinyl chloride material, is different from Example 1 in that an equal amount of barium zinc stabilizer is used to replace the magnesium aluminum zinc intercalated hydrotalcite.
[0095] Comparative Example 4 is a high temperature resistant soft flame retardant polyvinyl chloride material, which is different from Example 1 in that magnesium aluminum zinc intercalated hydrotalcite is not used.
[0096] Comparative Example 5 is a high temperature resistant, soft, flame retardant polyvinyl chloride material, which differs from Example 1 in that no antioxidant is used.
[0097] Comparative Example 6 is a high temperature resistant soft flame retardant polyvinyl chloride material, which differs from Example 1 in that no antioxidant and magnesium aluminum zinc intercalated hydrotalcite are used.
[0098] Performance testing
[0099] Test 1: Aging performance
[0100] With reference to the standard UL2556-2021, a Type II ventilated aging chamber as required by the ASTM D5423 standard was adopted, with a ventilation frequency of 160 times / hour and aging was carried out at 158°C×168h.
[0101] Test 2: Tensile properties
[0102] Referring to the standard ASTM D638-2014, the tensile test was carried out using a micro-controlled electronic tensile testing machine with a tensile speed of 500 mm / min.
[0103] Test 3: DSC-TG test
[0104] The DSC-TG test was performed in a nitrogen (N2) atmosphere from room temperature to 600°C at a heating rate of 10°C / min.
[0105] Test 4: Thermal stability
[0106] According to GB / T 2951.32-2008, a high temperature test of 200°C was carried out on the test sample to test the thermal stability time of the test sample. The test sample was a narrow strip with a length of 20-30 mm.
[0107] Test 5: Flame retardant properties
[0108] Flame retardant passed UL1581 single vertical combustion (VW-1).
[0109] Combustion requirement parameters
[0110] The cotton must be dry, pure, and of uniform thickness, not exceeding 6mm.
[0111] Methane gas: industrial grade methane; purity not less than 98%; calorific value 37±1MJ / m 3 ; Gas pressure should be 700-1400Kgf / cm 2 between.
[0112] Blowtorch (igniter): meets the requirements of ASTM D5025-12; tube length 100±10mm; tube inner diameter 9.5±0.3mm.
[0113] Standard flame requirements: flame power 500W (1700BTU / h); total flame height 125±10mm; blue inner flame height 40±2mm.
[0114] Combustion chamber requirements: should be airtight, with a total volume of no less than 4m 3 (140ft 3 ). The space above the gas flame should be at least 2m3 (70ft3), the distance between any straight line inside should be 610mm. There should be no obstacles under the flame to block the free flow of gas and affect the oxygen supply to the flame. The blowtorch (igniter) is placed on the wedge block, and the distance between the indicator flag and the top of the combustion chamber is at least 1.2m (4ft); the distance between the blowtorch (igniter) outlet and the inner flame tip (i.e. the contact point with the wire) is 40mm.
[0115] Burning test samples: 3 samples with a minimum length of 610 mm are cut from finished cables and insulated core wires in cables that have been left for more than 6 hours.
[0116] Indicator flag: Use kraft paper weighing 94g / ㎡, with a width of 12.5±1mm and a thickness of 0.13mm (5mi1). Single-sided adhesive, wrapped on the wire in a flag shape, with the backs sticking together and extending 20mm. The distance between the bottom edge of the indicator flag and the tip of the inner flame is 250mm.
[0117] Combustion Test Procedure
[0118] First, turn on the power switch of the air compressor, and then rotate the control door switch to the open position (that is, the air intake window and exhaust window are opened and the exhaust fan automatically extracts and exhausts air).
[0119] Turn on the switch of the methane cylinder, slowly open the flow meter until it reaches the specified scale, and then observe whether the U-tube scale is normal. If it is normal, light the blowtorch. (For details of the flow meter scale and U-tube scale, see the calibration results).
[0120] After the flame has burned for 5 minutes, use a caliper (or other measuring tool) to check whether the height of the inner and outer flames meets the requirements.
[0121] Fix the sample on a vertical support so that the longitudinal axis of the sample is vertical, and stick the indicator flag to the sample as required. The bonding position is the position specified by the indicator ruler on the support (i.e., the position from the point where the inner flame tip contacts the wire to the lower edge of the indicator flag is 250mm).
[0122] Lay a layer of cotton under the sample, with the foot of the sample as the center of the circle, within the range of 150-200mm (6-8in) in diameter.
[0123] Rotate the control door switch to close the combustion box door window and the inlet and exhaust windows, then turn on the timer switch, and slowly rotate the blowtorch holder to the left to the designated position through the glove hole in the operation window to supply fire and burn. At the same time, the timer switch is automatically started and the timing begins. Each time the fire is burned for 15 seconds, then the blowtorch holder is quickly rotated to the right and away from the wire for 15 seconds (not 15 seconds to extinguish the fire). If the previous flame is not extinguished, the second flame supply will not be applied. Each sample is subjected to a total of 5 fire supply and combustion tests.
[0124] After the combustion of each sample is completed, rotate the control door switch to the open position to extract air.
[0125] Record the combustion (spontaneous combustion) time of the sample each time the blowtorch is removed, the burning condition of the indicator flag, and the ignition condition of the cotton.
[0126] If the combustion test (stop) is over, first turn off the flow meter switch and the timer power switch, and then turn off the methane cylinder switch and the air compressor switch in turn.
[0127] Combustion determination
[0128] After applying a standard flame of 15 seconds five times, the burning time after any flame application shall not exceed 60 seconds, and the indicator flag shall not be burned by more than 25%, and there shall be no dripping objects igniting the cotton (if any dripping objects or hot particles fall outside the cotton padding area or on the fixture during the combustion process, the test result shall be invalid and re-sampling and testing shall be required). If all three test items are met, it shall be judged as qualified; if there is one unqualified item, it shall be retested after 24 hours for all six items. If all of them are qualified, it shall be judged as qualified; if there are still unqualified items, it shall be judged as unqualified; if two unqualified items are met, it shall be directly judged as unqualified.
[0129] Test samples: The high temperature resistant, soft, flame retardant polyvinyl chloride materials of Examples 1 to 19 are used as example samples; the high temperature resistant, soft, flame retardant polyvinyl chloride materials of Comparative Examples 1 to 6 are used as comparative examples.
[0130] Test results: The test results of thermal stability, flame retardant properties and tensile properties before and after aging of the high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 1 to 19 and Comparative Examples 1 to 6 are shown in Table 4.
[0131] Table 4. Test results of thermal stability, flame retardancy and tensile properties before and after aging of high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 1 to 19 and Comparative Examples 1 to 6
[0132]
[0133]
[0134]
[0135] Combined with Examples 1 to 19, Comparative Examples 1 to 6 and the attached Figure 1 To Attachment Figure 4, and combined with Table 4, it can be seen that: the initial decomposition temperature in the TG test results, the first stage endothermic peak and the second stage endothermic peak in the DSC test results, the tensile strength before and after aging and the elongation at break of the high temperature resistant soft flame retardant polyvinyl chloride material of Example 1 are higher than those of Comparative Example 1 and Comparative Example 2, indicating that the use of a higher number of plasticizer systems and an appropriate amount of magnesium aluminum zinc intercalated hydrotalcite can improve the toughness, thermal stability, aging performance and mechanical properties of the high temperature resistant soft flame retardant polyvinyl chloride material; it may be because a larger number of plasticizers promotes the dispersibility and compatibility of magnesium aluminum zinc intercalated hydrotalcite, antioxidant, filler and flame retardant in PVC resin; further, the magnesium aluminum zinc intercalated hydrotalcite has an interlayer structure, which can improve the stability of the antioxidant, so that the prepared high temperature resistant soft flame retardant polyvinyl chloride material has good thermal stability, flexibility, flame retardancy, aging resistance and mechanical properties.
[0136] The initial decomposition temperature in the TG test results, the first stage endothermic peak and the second stage endothermic peak in the DSC test results, the tensile strength before and after aging and the elongation at break of the high temperature resistant soft flame retardant polyvinyl chloride material of Example 1 are higher than those of Comparative Examples 3 to 6. This may be because the antioxidant and magnesium aluminum zinc intercalated hydrotalcite are used in the raw materials of the high temperature resistant soft flame retardant polyvinyl chloride material, which have a good compatibility effect, thereby improving the antioxidant performance and thermal oxygen stability of the high temperature resistant soft flame retardant polyvinyl chloride material; it may be because the magnesium aluminum zinc intercalated hydrotalcite has an interlayer structure, has heat resistance, heat insulation and good chemical stability effects, and the antioxidant can migrate to the interlayer structure of the magnesium aluminum zinc intercalated hydrotalcite, further improving the stability of the antioxidant, improving the stability of the high temperature resistant soft flame retardant polyvinyl chloride material, reducing the volatilization and degradation of the toughening agent during the processing, and then improving the toughening effect, so that the prepared high temperature resistant soft flame retardant polyvinyl chloride material not only has good stability to heat, light and free radicals, but also has good flexibility, flame retardant properties and mechanical properties.
[0137] From the perspective of molecular structure, the PVC molecular chain contains polar carbon-chlorine bonds, and the resin is porous. The process of plasticizer entering the PVC matrix includes electrostatic forces such as van der Waals forces and gradual diffusion. Its thermal aging process includes the degradation of the matrix resin and the volatilization and migration of the plasticizer. After testing, the flash point of TOTM used in the embodiment of this application is 242°C, the flash point of polyester plasticizer W-797 is 265°C, and the flash point of tetraoctyl pyromellitic acid is 270°C. The effects of plasticizers and EVA on the thermal degradation process of PVC in N2 atmosphere are shown in the attached figure. Figure 1 shown.
[0138] By the attached Figure 1From the TG and DSC curves, it can be seen that the initial decomposition temperature of PVC using TOTM plasticizer is 184.6℃, and the endothermic peak temperatures of the two stages are 281.0℃ and 452.2℃; the corresponding temperatures of polyester plasticizer W-797 are increased to 192.2℃, 304.2℃, and 466.3℃; the corresponding temperatures of tetraoctyl pyromellitic acid are increased to 193.7℃, 308.2℃, and 477.4℃; the corresponding temperatures of tetraoctyl pyromellitic acid compounded with EVA reach 199.0℃, 307.0℃, and 477.3℃. In general, the higher the flash point of the plasticizer, the better the heat resistance of the PVC material. Using EVA instead of 50% polyester plasticizer can reduce the volatilization of the plasticizer and increase the initial decomposition temperature of the PVC material, which has a good compatibility effect, and the high temperature resistant soft flame retardant polyvinyl chloride material prepared has good thermal stability.
[0139] The influence of plasticizer on the mechanical properties of PVC before and after accelerated aging is shown in the attached figure. Figure 2 As shown: the tensile strength of the PVC material before aging fluctuates around 16.5MPa, the elongation at break fluctuates around 300%, the amount of stabilizer added is 12.5phr, the PVC material using TOTM plasticizer has become brittle after aging, and the retention rate of elongation at break is only 22%, which is increased to 78% and 83% after replacing polyester plasticizer W797 and tetraoctyl pyromellitic acid, and the retention rate of elongation at break reaches 91% by using tetraoctyl pyromellitic acid compounded with EVA. The use of high flash point plasticizer and compounded EVA can significantly improve the mechanical properties of PVC material after aging, and the prepared high temperature resistant soft flame retardant polyvinyl chloride material has good flexibility and mechanical properties.
[0140] The effect of the amount of MgAlZn intercalated hydrotalcite on the thermal degradation of PVC in N2 atmosphere is shown in the attached figure. Figure 3 As shown: From the TG curve, it can be seen that when the temperature is lower than 220℃, the mass loss rate is within 2%, and the small molecular gas produced by the decomposition of PVC is basically absorbed by the magnesium-aluminum-zinc intercalated hydrotalcite; the first stage of PVC decomposition is from 220℃ to 390℃, and the mass loss rate exceeds 50%. In this stage, the main reaction of PVC self-catalytic decomposition to release HCl and form a conjugated polyene structure in the molecular chain; the second stage of PVC decomposition is from 390℃ to 600℃, and the mass loss rate is about 20%, and the molecular chain cracking, cyclization and aromatization reactions occur.
[0141] Under the condition of keeping the additive content the same, as the dosage of magnesium aluminum zinc intercalated hydrotalcite increases from 5phr to 15phr, the mass retention rate of the first stage increases from 48.5% to 50.0%, and the mass retention rate of the second stage increases from 28.3% to 31.7%. This is because the mechanism of action of magnesium aluminum zinc intercalated hydrotalcite is to absorb HCl released by the decomposition of PVC, and form a complex with the unstable chlorine atoms in PVC to couple the PVC molecular chain, thereby improving the thermal stability of the PVC substrate.
[0142] By the attached Figure 3 From the DSC curve, it can be seen that when the dosage of Mg-Al-Zn intercalated hydrotalcite increases from 5phr to 15phr, the endothermic peak of the first stage increases from 303.7℃ to 307.7℃, and the endothermic heat decreases from 140.2J / g to 82.4J / g; the endothermic peak of the second stage increases from 471.5℃ to 477.4℃, and the endothermic heat decreases from 20.2J / g to 12.4J / g. The temperature ranges of the two absorption peaks and the two degradation stages of the TG curve are roughly the same, the absorption peak moves toward the high temperature direction, and the endothermic heat decreases, indicating that Mg-Al-Zn intercalated hydrotalcite can effectively improve the heat resistance of PVC.
[0143] The effect of the amount of magnesium-aluminum-zinc intercalated hydrotalcite on the mechanical properties of PVC before and after accelerated aging is shown in the attached figure. Figure 4 As shown: the tensile strength of the PVC material before aging fluctuates around 16.5MPa, and the elongation at break fluctuates around 295%. As the amount of magnesium-aluminum-zinc intercalated hydrotalcite increases from 5phr to 15phr, the tensile strength retention rate after aging increases from 62% to 96%, and the elongation at break retention rate increases from 26% to 87%.
[0144] The initial decomposition temperature in the TG test results, the first stage endothermic peak and the second stage endothermic peak in the DSC test results, the tensile strength and elongation at break before and after aging of the high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 16 to 18 are higher than those of Examples 1 to 15, indicating that the magnesium aluminum zinc intercalated hydrotalcite used in the high temperature resistant soft flame retardant polyvinyl chloride material is modified by polydopamine and epoxy silane coupling agent, which improves the thermal stability, flexibility and mechanical properties of the high temperature resistant soft flame retardant polyvinyl chloride material; it may be because the surface of the magnesium aluminum zinc intercalated hydrotalcite is modified by polydopamine and silane coupling agent, which improves the dispersibility of the magnesium aluminum zinc intercalated hydrotalcite in the PVC substrate, and the polar groups in polydopamine and silane coupling agent enhance the interaction between the modified magnesium aluminum zinc intercalated hydrotalcite and other components, thereby improving the thermal stability, flexibility and mechanical properties of the high temperature resistant soft flame retardant polyvinyl chloride material.
[0145] Table 5. Test results of other properties of high temperature resistant soft flame retardant polyvinyl chloride materials of Examples 1 to 19
[0146]
[0147] The high temperature resistant, soft, flame-retardant polyvinyl chloride material of the embodiment of the present application can withstand bending at a low temperature of -40°C, and can withstand high temperatures up to 125°C, which is better than the provisions of the industry standard UL758-2022 "Safety Standards for Electrical Wiring Wires and Cables".
[0148] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A high temperature resistant, soft, flame retardant polyvinyl chloride material, characterized in that: In parts by mass, the raw materials include: 100 parts of PVC resin, 80-95 parts of plasticizer system, 5-15 parts of magnesium aluminum zinc intercalated hydrotalcite, 0.1-1 parts of antioxidant, 10-15 parts of filler, 13-50 parts of flame retardant and 0.2-0.6 parts of lubricant; The plasticizing system is a composition of EVA and polyester plasticizer in a mass ratio of (0.05-1.2):1; The polyester plasticizer is at least one of polyester plasticizer W-797, tetraoctyl pyromellitate, trioctyl trimellitate, di(2-propylheptyl)phthalate, and undecyl phthalate; The antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, tris(2,4-di-tert-butylphenol) phosphite, and β-dodecylthiopropionate pentaerythritol ester; The magnesium-aluminum-zinc intercalated hydrotalcite is treated with a treatment solution for 20-30 hours, and then filtered, washed, and dried to obtain a modified magnesium-aluminum-zinc intercalated hydrotalcite; The treatment liquid includes 1-3 kg / L of dopamine, 0.3-0.6 kg / L of epoxy silane coupling agent and 1-1.5 kg / L of ammonium persulfate, and the pH value is adjusted to 8-9; The preparation method of the high temperature resistant soft flame retardant polyvinyl chloride material comprises the following steps: Mix PVC resin, polyester plasticizer, magnesium aluminum zinc intercalated hydrotalcite, antioxidant, filler, flame retardant and lubricant, stir at high speed, and heat to 115-125°C; then cool to 70-90°C, add EVA, stir and mix to obtain a mixture; The mixture is melt-extruded, granulated and cooled to prepare a high-temperature resistant, soft and flame-retardant polyvinyl chloride material; the temperature of the melt-extrusion is 130-185°C.
2. The high temperature resistant, soft, flame retardant polyvinyl chloride material according to claim 1, characterized in that: The lubricant is a composition of neutral ester wax and oxidized polyethylene wax.
3. The high temperature resistant, soft, flame retardant polyvinyl chloride material according to claim 2, characterized in that: The lubricant is 0.1-0.3 parts of neutral ester wax and 0.1-0.3 parts of oxidized polyethylene wax; The neutral ester wax is at least one of dicarboxylic acid esters of saturated fatty alcohols, butyl stearate, glyceryl monostearate, and pentaerythritol stearate.
4. The high temperature resistant, soft, flame retardant polyvinyl chloride material according to claim 1, characterized in that: The flame retardant is 3-9 parts of antimony trioxide, 5-25 parts of magnesium hydroxide and 5-16 parts of aluminum hydroxide; The filler is at least one of calcium carbonate, kaolin and talc.
Citation Information
Patent Citations
Wear-resisting flame-retardant polyvinyl chloride insulation and sheathing materials
CN102719040A
Polymer composition
US20190300692A1